Different antiplatelet regimens for stenting versus coiling for acutely-ruptured cerebral aneurysms - Li Li; Qing-Hai Huang; Qiu-Ji Shao; Kai-Tao Chang; Qian-Qian Zhang; Liang-Fu Zhu; Jian-Min Liu; Tian-Xiao Li; Bu-Lang Gao (Scientific Reports)
Abstract To investigate the safety, efficacy and risk factors for complications of stenting with optional coiling versus coiling alone for acutely ruptured cerebral aneurysms (ARCAs) using different antiplatelet schemes, 2021 patients were prospectively enrolled into the stenting group (n = 967) and the coiling group (n = 1054). Four different antiplatelet regimens were used. The clinical and treatment data were analyzed and compared. In the stenting group, the common antiplatelet regimen was applied in 259 patients (26.8%), loading regimen in 210 (21.7%), intravenous tirofiban regimen in 240 (24.8%), and premedication free regimen in 258 (26.7%). The aneurysm occlusion degrees in the coiling vs. stenting group were not significantly (P > 0.05) different after treatment. Complications occurred in 168 (15.94%) and 171 (17.68%) patients in the coiling and the stenting group, respectively. Fifteen (1.55%) patients experienced stent-related ischemic complications. The only significant (P < 0.05) independent protective factor for complete occlusion was stent-assisted coiling in the stenting group but aneurysm daughter sac in the coiling group. Significant (P < 0.05) independent risk factors for poor mRS (3–6) were posterior circulation aneurysms and neurological bleeding complications in the stenting group and neurological complications in the coiling group. In the stenting group, the only independent risk factor was parent artery stenosis for neurological complications, Raymond grade III for neurological ischemic complications, and the ice cream technique for total complications in the stenting group. In conclusion, different antiplatelet schemes can be safely and efficiently used for intracranial stenting with optional coiling as compared with coiling alone for ARCAs.